2000
DOI: 10.1046/j.1365-313x.2000.00752.x
|View full text |Cite
|
Sign up to set email alerts
|

The TATA motif, the CAA motif and the poly(T) transcription termination motif are all important for transcription re‐initiation on plant tRNA genes

Abstract: SummaryThe effect of alteration of 5¢ and 3¢¯anking sequences on the transcription of plant tRNA genes was analysed using an RNA polymerase III-dependent in vitro transcription system derived from nuclei of cultured tobacco cells. A TATA-like sequence and the CAA motif frequently observed upstream of plant tRNA genes, and the poly(T) stretch usually present downstream, were shown to be necessary for ef®cient re-initiation of transcription. The CAA motif was shown to be a transcription initiation site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
60
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 41 publications
(73 reference statements)
4
60
0
Order By: Relevance
“…1B): (i) the information content is higher at TATA for S. pombe, (ii) the information content is higher at position 10 (greater propensity for G10) in A. thaliana, and (iii) the information content is higher around ϩ1 for A. thaliana. The A. thaliana pattern is consistent with data that show partial or little effect of TATA mutations but larger effects of CAA mutations on plant tRNA expression (9,81). Thus, the cumulative evidence indicates that although fission yeasts and plants exhibit TATA elements upstream of their tRNA genes, S. pombe is more obligatorily dependent on the TATA promoter element for transcription.…”
Section: Species Specificity Of Pol Iii-dependent Trna Transcriptionsupporting
confidence: 87%
See 2 more Smart Citations
“…1B): (i) the information content is higher at TATA for S. pombe, (ii) the information content is higher at position 10 (greater propensity for G10) in A. thaliana, and (iii) the information content is higher around ϩ1 for A. thaliana. The A. thaliana pattern is consistent with data that show partial or little effect of TATA mutations but larger effects of CAA mutations on plant tRNA expression (9,81). Thus, the cumulative evidence indicates that although fission yeasts and plants exhibit TATA elements upstream of their tRNA genes, S. pombe is more obligatorily dependent on the TATA promoter element for transcription.…”
Section: Species Specificity Of Pol Iii-dependent Trna Transcriptionsupporting
confidence: 87%
“…A CAA motif was noted to be a transcription initiation site for plant tRNA (81). The analysis in Fig.…”
Section: Species Specificity Of Pol Iii-dependent Trna Transcriptionmentioning
confidence: 96%
See 1 more Smart Citation
“…There are hybrid promoters like the U6 snRNA gene in S. cerevisiae that contain both internal promoters and a TATA box 61,62 which contributes to better transcription. 63,64,65 Microsatellites -The different microsatellites arrangements between genera at the NTS region are the main contributors to the variation in the NTS length. It has been shown that there is a correlation between the length of the NTS region and the number of motif repetitions within each region of microsatellites in Rajiformes.…”
Section: Nts Regionmentioning
confidence: 99%
“…24 and references therein). In some eukaryotic genomes, the upstream regions of ICR-containing class III genes are characterized by the presence of a TATA box, starting at around Ϫ30, which strongly contributes to transcription efficiency as an essential component of the promoter (25,26). In some cases, the upstream TATA element can even allow for TFIIIC-independent in vitro transcription (27,28).…”
mentioning
confidence: 99%